Exploring Persian Commercials Based on the Halliday’s Systemic-Functional Grammar - Rahimeh Roohparvar; Ali Asghar Rostami Abusaeedi; Fatemeh Deris (Iranian Journal of Applied Language Studies, 2015)
Advertisement has long been used as a tool for informing and attracting audiences in different ways. This study aims at investigating the linguistic tools of advertisement in Persian on the basis of Halliday’s systemic-functional grammar theory. The data of this study were gathered from written and verbal commercial advertisements which were recorded and rewritten in order to investigate verbal groups in the sentences in terms of process and function types and subsequently compare the two bodies. The results showed that material and relational processes had highest frequency in Persian language in terms of ideational metafunction. From the interpersonal metafunction perspective, information function was frequent in most cases. Regarding these factors, there was no significant difference between verbal and written bodies.